ANALYSIS OF THE IMPLEMENTATION OF THE WHISTLEBLOWING SYSTEM IN THE KENDARI CITY GOVERNMENT - Andriansyah, Rizaldi Tri; Widianingsih, Ida; Karlina, Nina (Universitas Padjadjaran, 2024)
The whistleblowing system is becoming an increasingly utilized tool worldwide to prevent and detect current violations. However, its implementation is not easy, as individuals require a sense of security and safety guarantees to be willing to participate in preventing violations and corruption. Therefore, adequate structures and processes are needed for its implementation. Kendari City is the only local government in the Southeast Sulawesi Province region that has implemented a whistleblowing system in its administration. This research aims to analyze the structure, mechanisms, and procedures of the whistleblowing system that has been implemented using best practices established by the Deputy of Investigation at the Financial and Development Supervisory Agency. The research employs a qualitative approach, utilizing document studies, observations, and interviews with individuals involved or directly engaged in implementing the whistleblowing system in the Kendari City government. The results indicate that the whistleblowing system implementation’s structure, mechanisms, and procedures have adhered to best practices in policy and institutional aspects as per the Technical Guidance Guidelines for the Implementation of the Thematic Fraud Control Plan System and Internal Whistleblowing Behavior.